165k views
2 votes
Does (2x^3+ 15x^2 +27x + 5)/2x+5= (x^2+5x+1). Justify your answer.

1 Answer

2 votes

Answer and explanation

We have given expression
(2x^3+15x^2+27x+5)/(2x+5)=x^2+5x+1

We have to prove this


(2x^3+15x^2+27x+5)/(2x+5)=x^2+5x+1 can be written as
{2x^3+15x^2+27x+5}={2x+5}* (x^2+5x+1)

Now we have to prove L.H.S = R.H.S

Lets take R.H.S

So
{2x+5}* (x^2+5x+1)=2x^3+10x^2+2x+5x^2+25x+5=2x^3+15x^2+27x+5 = L.H.S

Hence proved

User Chaney
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.